Definition of flood-prone areas: A comparison between HEC-RAS and Iber software results - Martins, Márcia (2020)
The availability of hydraulic modelling software allowing dynamic analysis of hydraulic variables behaviour, such as the water depth and flow velocity, is important for the assessment and management of flood-prone areas and, consequently, to reduce the associated risks. This study presents a comparison between the modelling results of a 1D (one-dimensional) and 2D (two-dimensional) hydraulic models-HEC-RAS and Iber software-in the definition of flood-prone areas for a sector of the Leça River (Northern Portugal). The main comparison refers to the maximum extent of the flood and the water depth, obtained from the mathematical simulation with these two free softwares, for return periods of 10, 50 and 100-years. Despite the two softwares consider different hydraulic approaches, it was recorded small differences in the extent of the flooded area and in the maximum water column height.